Game Edukasi Pengenalan Fungsi Organ Tubuh Manusia bagi Sekolah Dasar dengan Metode Scoring system - Aryaguna, Daffa; Santi, Rina Candra Noor (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
The introduction of the function of human organs is one of the science subject matter taught to elementary school students. However, there are still many students who have difficulty understanding and memorizing the material because of the many organs in the human body with different functions. Currently, the teacher still uses the conventional method where the teacher explains the material to students only through the media of books. In addition, the monotonous way of delivering the teacher is considered unattractive to students so that students do not easily understand the material taught by the teacher. Educational games can provide a fun atmosphere when learning, especially for elementary school students. This research is expected to make educational games for students to make it easier to understand school material, especially the introduction of human organs.. Educational games can provide a fun atmosphere when learning, especially for elementary school students. This research is expected to make educational games for students to make it easier to understand school material, especially the introduction of human organs. The method used is a scoring system with. The steps to determine the categorization begin by determining the statistical data descriptively including the minimum range (Xmin), maximum range (Xmax), wide distribution range, theoretical mean (μ) and standard deviation (σ). The results of this system show a categorization scale on each criterion and overall and produce three categories, namely bad, good, and very good. Categorization is used as a parameter of students' knowledge about the function of human organs with predetermined assessment categories.